Feasibility Test of Web-Based Video Modelling Media for Learning Social Skills for Autistic Students at Inclusive Elementary Schools in Surakarta - Wulandari, Novita Dwi; Sunardi, Sunardi; Yuwono, Joko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This research aims to know the feasibility level of Web-based Video Modelling Media for Social Skills of Autistic Students in Inclusive Elementary School in Surakarta. The current study used quantitative design as the research method. The test procedure used is Alpha Testing and Beta Testing. The subject of this research were autistic students at Inclusive Elementary School in Surakarta. The technique of data collection is done by a questionnaire. Data analysis using quantitative data analysis. The research results obtained were that Web-based Video Modeling Media for Social Skills of Autistic students received an assessment of 83.7% from media experts, 87.47% from material experts, and 88.5% from from IT experts and 89.01% from users candidate. So it can be infered that video modeling media for the social skills of autistic students is very decent for used to learning the social skills of autistic students in inclusive elementary schools in Surakarta